Retrospective study of cesarean section by using the Robson’s ten group classification system - Bhatt, Manoj; Kadikar, Gunvant; Parmar, Dipti C.; Kanani, Medha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The present study was done to determine the relative contribution of each of ten groups of robson´s classification to overall cesarean section rate and identify modifiable group for intervention to reduce the cesarean rate. Methods: Retrospective review of record of cesarean section from the statistical Dept of Obstetrics and Gynecology sir T. hospital, Bhavnagar from January 2017 to October 2017 and classify them in to Robson´s ten group classification system to find out total number of cesarean among total number of delivery in above 10 months duration. Results: Total number of delivery in my study institute in 10 months was 3804 out of them 1182 was cesarean section, so the overall cesarean section rate in Sir T. hospital, Bhavnagar was 31%. Group 1 (Nulliparous, single cephalic, >37 weeks in spontaneous labor), 2 (Nulliparous, single cephalic, >37 weeks, induced or CS before labor) and 5 (Previous CS, single cephalic, >37 weeks) contributes for around 66% of total cesarean. Group 5 (Previous CS, single cephalic, >37 weeks) was the major contributor among all. Least common cause of cesarean was group 8 (All multiple pregnancies (including previous CS)) and group 9 (All abnormal lies including previous CS). Conclusions: Incidence of cesarean was more common with patient having previous cesarean section. So, to decrease cesarean rate trial of labour should be given to the patient who was suitable for vaginal birth after cesarean section. Adequate assessment of pelvis and giving trial to patient having borderline pelvis also decrease the rate of cesarean in primi gravid (group 1).